2012 IEEE 17th International Workshop on Computer Aided Modeling and Design of Communication Links and Networks (CAMAD) 2012
DOI: 10.1109/camad.2012.6335308
|View full text |Cite
|
Sign up to set email alerts
|

Differenciated bandwidth allocation in P2P layered streaming

Abstract: Abstract-There is an increasing demand for P2P streaming in particular for layered video. In this category of applications, the stream is composed of hierarchically encoded sub-streams layers namely the base layer and enhancements layers. We consider a scenario where the receiver peer uses the pull-based approach to adjust the video quality level to their capability by subscribing to different number of layers. We note that higher layers received without their corresponding lower layers are considered as usele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…This paper extends our previous work [12] in many ways. It provides a more detailed description of the problem at hand and our solution approach including a mathematical analysis.…”
Section: Contributionssupporting
confidence: 78%
See 1 more Smart Citation
“…This paper extends our previous work [12] in many ways. It provides a more detailed description of the problem at hand and our solution approach including a mathematical analysis.…”
Section: Contributionssupporting
confidence: 78%
“…Authors in [12][11] [14] studied the impact of peers' upload bandwidth and established conditions for universal streaming for churnless systems. Furthermore, measurement studies and implementations [16] [17] confirmed that bandwidth has a big impact on streaming quality for P2P streaming systems.…”
Section: Related Workmentioning
confidence: 99%
“…In this case, the correct decision regarding the selection and the scheduling of the layers is crucial: how many layers to request, in which order and from which peer? In [4], we proposed amplitude and frequency reduction ( Figure 1) to ensure the smooth quality of the stream and bandwidth allocation schemes for layered streaming systems for P2P networks in [3]. The amplitude reduction mechanism aims to reduce the transition from the higher layer to very lower layer (amplitude reduction) and vice versa.…”
Section: Introductionmentioning
confidence: 99%